Immobilization of redox mediator for anaerobic biotransformation of congo red dye. - Olivo Alanís, Daniel Simón (2015)
Purpose and method of the study: About 50% of the dyes used for textile dyeing end up in the wastewater. It represents an ecotoxic hazard and introduces the potential danger of bioaccumulation, and can significantly damage the flora, fauna and the human health. Redox mediators have been applied on anaerobic digestion treatment to increase biotransformation of azo dyes, but its continuous addition causes a high cost for the treatment. For this reason, different immobilization techniques have been tried to obtain a solid-phase redox mediator. Nevertheless, to achieve high immobilization stability and to avoid detachment of redox mediator, different expensive and complicated methods of immobilization have been tested. In this work, two easy ways of covalently immobilization for redox mediator onto activated carbon were investigated, and their application for enhance decolorization of congo red dye at typical concentration of dye textile wastewater (150 - 200 mg/L). Contribution and Conclusions: Lawsone immobilization on granular activated carbon (GAC) was successfully achieved with high capacity (~1.56 mmol/g), and desorption studies shows chemical stability; immobilization conditions may suggest esterification mechanism between lawsone and activated carbon. Furthermore, an easy way for chlorination of activated carbon, duplicate adsorption capacity of AQDS onto chlorinated carbon, compared with adsorption on unmodified GAC, then nucleophilic substitution may covalently bonded sulfonate groups of AQDS onto activated carbon; both immobilization (physical and chemical) shows good stability. Kinetics with solid-phase redox mediator and their controls (GAC, GAC-Cl and anaerobic sludge) were proved for decolorization of congo red dye. Lawsone and AQDS immobilized on GAC reached ~85% and 87% of decolorization, compared to 28% reached by anaerobic sludge at 48 h. Gas chromatography show that methane production was slightly inhibited when redox mediator is applied. Moreover, selective hydrogen production was observed with GAC-Cl as redox mediator, duplicates and maintains the cumulative production compared to anaerobic sludge, attributed to a methanogenic inhibition and acid intermediates production. Finally, HPLC study shows a slow rate for benzidine production compared to decolorization; dye reduction mechanism is presented. Both synthetized solid-phase redox mediators are good candidates for application in continuous bioreactors